The Nexus Between Income Inequality and Environmental Degradation in ASEAN-6 Countries During 1992 – 2015 from Islamic Perspective - Nurrachmi, Rininta; Duasa, Jarita; Ariffin, Muhammad Irwan; Afroz, Rafia (Department of Islamic Economics, IPB University with the Indonesian Association of Islamic Economist (IAEI), 2024)
The purpose of the study is to examine the relationship between income inequality and environmental degradation in ASEAN-6 countries namely Indonesia, Malaysia, the Philippines, Thailand, Singapore, and Vietnam. It also provide analysis from the Islamic perspective based on result of the econometric regression. The study utilizes annual panel data from1992 until 2015 where the region suffered from high income distribution and environmental degradation. The analytical tool used in the study is Bias-Corrected Least Squared Dummy Variable (LSDVC), which is sufficient for small panel data. The methodological approach leads to two main findings. First, income inequality, measured by Gini coefficient, is contributing to environmental degradation (proxied by CO₂ emission and Natural Resources Depletion) in the short- and long-run term. Other explanatory variables namely GDP per capita and energy consumption, also impact significantly on environmental degradation level in the short- and long-term. From the findings, it is recommended that greater investment is required in addressing high level of income inequality and environmental issues. Instruments in Islam such as zakat and waqf provide solution to overcome issue of high income gap and environmental degradation in ASEAN-6 countries, moreover majority of Muslim population located in ASEAN countries. Hence, collaboration should be enhanced among the ASEAN-6 countries where wealth distribution, technology and knowledge sharing from high income countries to low and middle-income in ASEAN countries to mitigate the negative impact of high income inequality and environmental issue in the region